Unarmed Underground Organizations in the Town of Klaipėda in 1946–1953 - Pušinskytė, Lijana (Genocidas ir rezistencija, 2007)
The paper is concerned with unarmed underground organizations which were active in the town of Klaipėda from 1946 to 1953, which gave practical help to partisans.During the Second World War Klaipėda suffered huge material losses, and it had a very sparse population. Under such circumstances, there were almost no conditions to form an anti-Soviet resistance. From 1945 to 1946, the number of residents increased a chance to form anti-Soviet organizations. The Soviet security was not able to control people who held anti-Soviet views as strictly as before. Young people who had come to the town to study or work from the neighbouring regions were the most active, as were people who kept in touch with participants in the active resistance. All this furthered the formation of unarmed organizations in Klaipėda. Until the end of the partisan war the initiators and founders of such organizations were members in the armed resistance.Between 1946 and 1953, there were four secret unarmed organizations in the city, which kept in touch with the partisan units of the Žemaičiai and Kęstutis apygardos (military districts).The membership of the groups in Klaipėda was not numerous. Between 1946 and 1953, there were from 58 to 78 members in the four organizations. All of them were on trial, and 29 participants in the secret activities were sentenced from 6 to 25 years in prison.
Keywords: Klaipėda; anti-Soviet resistance; underground organizations